Proposed agronomic trials in the case study areas of ILCA Sub-Humid Programme, 1980 growing season - Mohamed-Saleem, M.A. (International Livestock Centre for Africa, 1980)
Outlines the various agronomic trials to be carried out by ILCA's Subhumid Programme in Abet & Kurmin Biri case study areas in Nigeria.